Voltammetric sensors modified with nanomaterials: applications in rapid detection of bioactive compounds for health and safety monitoring - Mohammad Harun-Ur-Rashid; Abu Bin Imran; Tahmina Foyez (Discover Electrochemistry)
Abstract The rapid detection of bioactive compounds is essential for health monitoring and safety assurance in clinical, environmental, and food analysis. Nanomaterial-modified voltammetric sensors have emerged as powerful tools for the sensitive and selective detection of key biomarkers, including dopamine, uric acid, ascorbic acid, and serotonin. This review highlights recent advancements in sensor design, emphasizing the role of carbon-based nanostructures, metal and metal oxide nanoparticles, and composite materials in enhancing electrocatalytic activity, surface area, and electron transfer rates. Key electrode fabrication techniques and signal enhancement mechanisms are discussed, alongside their applications in medical diagnostics, food safety, and environmental monitoring. Despite their advantages, challenges such as reproducibility, biocompatibility, and long-term stability persist. Future directions including integrating these sensors with digital platforms for real-time, on-site analysis, are addressed. This review explores the transformative potential of nanomaterial-enhanced voltammetric sensors in advancing rapid bioactive compound detection for improved public health and safety. Graphical Abstract